PRISM III Score Predicts Short-Term Outcome in Children with ARDS on Conventional and High-Frequency Oscillatory Ventilation - Snezana Rsovac; Davor Plavec; Dusan Todorovic; Aleksa Lekovic; Teja Scepanovic; Marija Malinic; Mina Cobeljic; Katarina Milosevic (MDPI AG, 2022)
Therapeutic recommendations for pediatric acute respiratory distress syndrome (PARDS) include conventional (CMV) and rescue high-frequency oscillatory mode (HFOV) of mechanical ventilation (MV). The pediatric risk of mortality (PRISM) is a frequently used mortality score for critically ill patients. In search of methods to recognize those patients, we analyzed the PRISM III score as a potential predictor of the short-term outcome in MV subjects with PARDS. A retrospective five-year study of PARDS in children on MV was conducted in the Pediatric ICU. Seventy patients were divided into two groups (age group <1 year and age group 1-7 years). The PRISM III score was used to assess the 28-day outcome and possible development of complications. The most common causes of PARDS were pneumonia and sepsis. Male sex, malnourishment, sepsis, and shock were significant indicators of poor outcome. The PRISM III score values were significantly higher in those who died, as well as in subjects requiring HFOV. The score had a significant prognostic value for short-term mortality. There was no significant difference in outcome based on the comparison of two modes of ventilation. A significantly higher score was noted in subjects who developed sepsis and cardiovascular insufficiency. The PRISM III score is a fair outcome predictor during the 28-day follow-up in MV subjects with PARDS, regardless of the ventilation mode.